2017
DOI: 10.1038/s41598-017-04252-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating Zinc levels in Parkinson’s disease: a meta-analysis study

Abstract: There is no consensus on the involvement of zinc (Zn) dysfunctions in Parkinson’s Disease (PD). We performed a meta-analysis to evaluate whether circulating Zn levels in the serum, plasma, and cerebrospinal fluid (CSF) are altered in PD. Twenty-three published studies were selected by searching the databases of PubMed and China National Knowledge Infrastructure (CNKI). A total of 803 PD patients and 796 controls, 342 PD patients and 392 controls, and 135 PD patients and 93 controls were included to study Zn le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 49 publications
2
28
1
Order By: Relevance
“…Zinc supplementation can boost MT expression throughout the body, via binding to metal-responsive transcription factor-1, a phenomenon reflecting the fact that MT also provides protection from intracellular zinc excess [198][199][200]. A number of case-control studies have found that serum zinc levels are lower in PD patients than in matched healthy controls, as confirmed by meta-analysis [201,202]. The impact of zinc supplementation on risk for or control of PD, in rodents or humans, does not appear to have been assessed.…”
Section: Scavenging Peroxynitrite-derived Radicals-benefits Of Supplementioning
confidence: 86%
“…Zinc supplementation can boost MT expression throughout the body, via binding to metal-responsive transcription factor-1, a phenomenon reflecting the fact that MT also provides protection from intracellular zinc excess [198][199][200]. A number of case-control studies have found that serum zinc levels are lower in PD patients than in matched healthy controls, as confirmed by meta-analysis [201,202]. The impact of zinc supplementation on risk for or control of PD, in rodents or humans, does not appear to have been assessed.…”
Section: Scavenging Peroxynitrite-derived Radicals-benefits Of Supplementioning
confidence: 86%
“…Numerous markers have been investigated to evaluate oxidative stress in PD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 55 ] ( Table 1 and Table 2 ); however, meta-analysis showed that only five CSF oxidative stress markers, 8-hydroxy-2’-deoxyguanosine (8-OHdG), Mn, Cu, Zn, and Fe, could be evaluated, and no significant difference was found between PD patients and controls [ 13 ]. On the other hand, the meta-analysis showed that patients with PD had significantly higher levels of blood oxidative stress markers compared with healthy control subjects for ferritin, 8-OHdG, nitrite, and malondialdehyde; meanwhile, the concentrations of uric acid, catalase, glutathione, and total-cholesterol were significantly lower in PD patients compared with healthy control subjects [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other markers (advanced oxidized protein products (self-oxidized), ceruloplasmin ferroxidase activity, oxidized Q10, Cu/Zn-superoxide dismutase, DJ-1, glutathione S-transferase Pi, glutathione (oxidized), hydroxy radical ( · OH), lipid peroxidation, nitrites, nitrates, silicic acid, xanthine, 3-nitrotyrosine products, and 8-hydroxyguanosine (8-OHG)) have also been investigated [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…While ATP13A2 was not identified as a hit through our screen, silencing of that gene resulted in a trend towards increased a-synuclein cell-to-cell transfer. Reduced zinc levels in the serum and plasma have also been found in advanced forms of PD (Du et al, 2017). The exact mechanism with which zinc modulates the cell-to-cell transfer of a-synuclein remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%